2019
DOI: 10.1108/ijph-01-2019-0002
|View full text |Cite
|
Sign up to set email alerts
|

Justice-involved women’s preferences for an internet-based Sexual Health Empowerment curriculum

Abstract: Purpose The purpose of this paper is to gain insight into justice-involved women’s preferences for an internet-based Sexual Health Empowerment (SHE) curriculum. Design/methodology/approach The authors analyzed data from four focus groups conducted with 52 women in a minimum-security county jail in a Midwestern US city. Findings Women reported daily access to the internet while in the community and use of the internet for searching about health concerns. Four themes emerged in the discussion about preferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…We observed that most of the research conducted on sexual health education focused on HIV infections as the primary concern, and literature [43] has indicated that providing general education and case management services enhances retention in treatment.…”
Section: Hiv and Other Sexually Transmitted Infectionsmentioning
confidence: 93%
See 1 more Smart Citation
“…We observed that most of the research conducted on sexual health education focused on HIV infections as the primary concern, and literature [43] has indicated that providing general education and case management services enhances retention in treatment.…”
Section: Hiv and Other Sexually Transmitted Infectionsmentioning
confidence: 93%
“…On the other hand, few studies indicate that women leaving prison prefer multimedia interactions [43]. In contrast, other studies suggest that health information delivered via video is more likely to lead to a change in preventive behavior than traditional methods (pamphlets), especially for audiences with less health education [44].…”
Section: Women's Health and Techniques For Health Education And Promo...mentioning
confidence: 99%
“…Lastly, while no previous research was identified explicitly demonstrating a decided student preference for a women's health instructor on the basis of gender within higher education, some participants of a justiceinvolved female sexual health empowerment curriculum focus group stated a decided preference for a female instructor. 13 The question of whether pharmacy students find a male instructor teaching on female intimate treatments embarrassing or improper remains unanswered. This report describes an instance in which, as a result of pre-established faculty workload delegation, male faculty were assigned to deliver the majority of female-specific sex and gender health topics in a pharmacy curriculum at a small, private, not-for-profit college of pharmacy in Southern California.…”
Section: Introductionmentioning
confidence: 99%
“…29 Previous research has found a preference for multimedia among women leaving jail, specifically; such an intervention has the advantage of rapid deployment, tailoring, and low-cost scalability. 30 Video has gained renewed interest lately as an enhanced method to promote health literacy, either through sharing of user experiences, [31][32][33] or through dedicated health education to increase knowledge and comprehension. 34 Health information presented as video has also been shown to lead to greater behavior change related to preventive screening compared with traditional methods (pamphlets and flyers), especially for audiences with lower health literacy 35,36 (defined as adults who have difficulties in obtaining, understanding, and acting on health information and services, and also have decreased ability to make appropriate health decisions on their own).…”
mentioning
confidence: 99%